ANALISIS SEBARAN LOGAM TANAH JARANG UNTUK PENGEMBANGAN WILAYAH PERTAMBANGAN MENGGUNAKAN CITRA LANDSAT-9 DI KABUPATEN BANGKA SELATAN: ANALYSIS OF RARE EARTH METAL DISTRIBUTION FOR MINING AREA DEVELOPMENT USING LANDSAT-9 IMAGES IN SOUTH BANGKA REGENCY - Sulka Wijaya; Mega Rosana Fatimah; Euis Tintin Yuningsih; Armin Tampubolon (Buletin Sumber Daya Geologi, 2023)
The development of high technology currently relies heavily on rare earth elements (REE), some of which are obtained from tin ore mining. The largest production of tin ore is located in the Bangka Belitung Islands. To assess this potential further, this research aims to provide direction for development. The focus of this research centers on Monazite, which has the potential to be processed into rare earth elements, currently in high demand across various global industries and expected to see increasing demand. Monazite is a by-product of tin ore processing. Tin mining in Bangka Island, in general, and South Bangka Regency, in particular, has a long history dating back to the Dutch occupation period and continues to the present day. Geologically, the presence of Triassic-age granite is associated with tin formation, stretching from the Peninsula of Thailand-Malaysia-Riau Islands to Bangka-Belitung and West Kalimantan, known as the Granite Tin Belt. This is indicated by the presence of associated minerals such as Monazite, Xenotime, and zircon, which play a strategic role as REE sources. Regions abundant in mineral resources require proper regional planning to ensure optimal management and utilization. This study refers to the research results conducted by the Coal and Geothermal Mineral Resources Center (PSDMBP) in 2009, 2014, and 2018, which were compared with Landsat-9 images. The purpose of this research is to identify potential areas suitable for developing the Rare Earth Elements (REE) mining industry in South Bangka. The research methodology employs qualitative descriptive analysis and spatial analysis. The analysis results indicate the suitability of spatial utilization for mining activities in Rindik Village and Keposang Village, confirmed through on-site sampling to substantiate their potential. The presence of Monazite in over 50% of the total tailings samples suggests that the area can be developed into a Mining Business Area for REE commodities